International Monetary Fund Annual Report 2003 : Making the Global Economy Work for All. (Annual Report of the Executive Board; Annual Report of the Executive Board, 2003)
This 2003 Annual Report highlights that during FY2003, the IMF held bilateral (country) discussions with 136 members. It also took a number of steps to enhance the effectiveness of its surveillance and crisis prevention work. Among these efforts, it continued to develop a system to assess countries' vulnerability to balance-of-payments crises. The Executive Board proposed improvements to assessment exercises under the IMF's standards and codes initiative and the joint IMF-World Bank Financial Sector Assessment Program (FSAP), and supported proposals to enhance data provision for surveillance.